Formation of the Y Feature at the Venusian Cloud Top by Planetary‐Scale Waves and the Mean Circulation: Analysis of Venus Express VMC Images. Issue 5 (2nd May 2019) - Nara, Y.; Imamura, T.; Murakami, S.; Kouyama, T.; Ogohara, K.; Yamada, M.; Takagi, M.; Kashimura, H.; Sato, N.
Abstract: The relationship between the planetary‐scale ultraviolet contrast known as the Y feature and the wind field at the Venusian cloud top was investigated by using images obtained by Venus Monitoring Camera (VMC) on ESA's Venus Express. Spectral analyses of the ultraviolet reflectivity and the wind field revealed common periodicities of 4–5 Earth days, which are attributed to Kelvin and Rossby waves with a zonal wave number of unity. Combined with the morphological relationship between the dark streaks and the enhancement of poleward flow, we propose a mechanism for the formation of the Y feature: The dark materials are supplied to the cloud top in the equatorial region by a Kelvin wave, subsequently advected poleward by the mean meridional circulation and a Rossby wave, and then stretched by the midlatitude jet to the tilted band structures. A simplified transport model was developed to demonstrate the scenario. Plain Language Summary: The albedo feature of Venus' cloud top is important for radiative energy budget and atmospheric chemistry. The Venus' cloud frequently exhibits planetary‐scale, equatorially symmetric dark patterns in ultraviolet, called the horizontal Y feature, which is composed of tilted dark bands extending from the equator to high latitudes and a dark equatorial band at the root of the Y. The generation mechanism of the feature has been unclear for more than 40 years since its discovery. This study proposes a mechanism based on an analysis of cloud images obtained by ESA's Venus Express. We have identified planetary‐scale waves with periods of 4–5 Earth days in the ultraviolet reflectivity and the wind field. The combination of those planetary‐scale waves and the mean circulation was shown to produce the Y feature using a simplified transport model. Key Points: The role of planetary‐scale winds in the formation of the Y feature was investigated using UV images taken by Venus Express 4‐ and 5‐day periodicities were found in the UV brightness and the wind velocity, suggesting the roles of atmospheric waves The tilted dark bands can be created by the transport of dark materials by Kelvin and Rossby waves and the mean circulation